Corporate Sustainability and Strategic Adaptation in Emerging Markets: Evidence from Sustainability and Annual Reports - Bunga Dwi Fani Ritonga (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines how corporations in emerging markets articulate and implement strategic adaptation to sustainability imperatives through evidence drawn from sustainability and annual reports. Using a qualitative content analysis of corporate documents published between 2020 and 2024, the research identifies patterns in disclosure practices, governance adaptation, and sustainability-linked financing. The findings reveal that although sustainability disclosures have become increasingly common, substantial heterogeneity persists in the depth of strategic integration and operational execution. Firms that embed sustainability objectives into governance structures, performance targets, and financing mechanisms demonstrate higher strategic maturity and resilience. The results also indicate that emerging-market corporations are progressively aligning with international reporting frameworks such as ISSB and EFRAG, signaling a broader institutional transformation. Overall, corporate documentation provides a valuable lens through which to observe the transition of emerging-market firms from symbolic reporting toward substantive strategic adaptation that integrates sustainability into long-term business competitiveness.